Laser Capture Microdissection-Generated Target Sample for High-Density Oligonucleotide Array Hybridization. (September 2000) - Ohyama, H.; Zhang, X.; Kohno, Y.; Alevizos, I.; Posner, M.; Wong, D.T.; Todd, R.
Current advances in biomolecular technology allow precise genetic fingerprinting of specific cells responsible for the pathogenesis of human diseases. This study demonstrates the feasibility of generating target samples from laser capture microdissection (LCM) tissues suitable for hybridization of high-density oligonucleotide arrays for gene expression profiling. RNA was successfully isolated by LCM from three paired specimens of oral cancer and linearly amplified using T7 RNA polymerase. Evaluation of the cDNA revealed that five of five cellular maintenance transcripts are detected. Biotinylated cRNA was generated and hybridized to the human Test 1 GeneChip ® probe arrays, which demonstrated that the RNA is of sufficient quality and integrity to warrant further analysis. Subsequent hybridization of the samples to the HuGenFL GeneChip probe arrays revealed that 26.5%–33.0% of the approximately 7000 represented genes are expressed in each of the six samples. These results demonstrate that LCM-generated tissues can generate sufficient quality cRNA for high-density oligonucleotide microarray analysis, an important step in determining comprehensive gene expression profiling using this high-throughput technology.